Analysis of a temperature-sensitive mutation in Uba1: Effects of the click reaction on subsequent immunolabeling of proteins involved in DNA replication - Sugaya, Kimihiko (FEBS Open Bio, 2015)
In our previous study, a Met-to-Ile substitution at amino acid 256 in the catalytic domain of Uba1 was determined in temperature-sensitive CHO-K1 mutant tsTM3 cells, which exhibited chromosomal instability and cell-cycle arrest in the S to G(2) phases with decreased DNA synthesis at the nonpermissive temperature, 39 °C. Mutant cells were also characterized by a significant decrease of Uba1 in the nucleus with decreased ubiquitination activity at 39 °C. Defects of ubiquitination activity in the nucleus resulted in an inappropriate balance between Cdt1 and geminin, a licensing factor of DNA replication and its inhibitor. In the present study, we found that the Cu(I)-catalyzed [3 + 2] cycloaddition (click) reaction inhibits the subsequent indirect immunolabeling of Cdt1 but allows for the detection of PCNA with nascent DNA. Using a procedure without the click reaction, we also demonstrated that Cdt1 remained close to active replication sites in tsTM3 cells at the nonpermissive temperature. Analysis of genome replication by DNA fiber spreading revealed that DNA synthesis continues for at least 10 h after incubation at 39 °C, suggesting that impaired ubiquitination in the nucleus, caused by the defect of Uba1, affected DNA replication only after a long delay.